A case study of PAH contamination using blue mussels as a bioindicator in a small Greenlandic fishing harbor. (October 2021) - Poulsen, Rikke; Gravert, Thorsten Klaus Otto; Tartara, Arianna; Bensen, Henriette Kornmaaler; Gunnarsen, Klara Cecilia; Dicová, Kristína; Nielsen, Nikoline Juul; Christensen, Jan Henning
Abstract: This study investigated the impact of local anthropogenic activity on the marine environment around the remote harbor of Qeqertarsuaq, West Greenland. Blue mussels ( Mytilus sp.) were used as a bioindicator, and their physiological condition was found to decrease with increasing proximity to the harbor. Subsequently, the distribution of 19 polycyclic aromatic hydrocarbons (PAHs) and 9 groups of alkylated PAHs were measured in mussel and sediment samples. The highest values were found in a rocky collection area 15 m from a wooden pier frequented by small boats. A PAH source investigation, indicated a mixed source from light fuel oils and creosote used as boat coating. Finally, correlations between the mussels morphological condition and the PAH pollution were found to be significant for 4-, 5-, and 6-ring PAHs. In conclusion, the results indicate that pollution sources in harbors have significant effects on the local environment and should be considered in arctic conservation research. Graphical abstract: Unlabelled Image Highlights: PAH were detected in mussel tissue and sediment in a small Greenlandic harbor. Local PAH contamination correlated negatively with blue mussel health. PAH source investigation indicated mixed pollution from creosote and light fuel oils.